If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + -48 = s Reorder the terms: -48 + 2s = s Solving -48 + 2s = s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. -48 + 2s + -1s = s + -1s Combine like terms: 2s + -1s = 1s -48 + 1s = s + -1s Combine like terms: s + -1s = 0 -48 + 1s = 0 Add '48' to each side of the equation. -48 + 48 + 1s = 0 + 48 Combine like terms: -48 + 48 = 0 0 + 1s = 0 + 48 1s = 0 + 48 Combine like terms: 0 + 48 = 48 1s = 48 Divide each side by '1'. s = 48 Simplifying s = 48
| 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 | | 84=78+n | | -x+7x=-12 | | -x^2+5=(4x-1)(4x-1) | | 4a+7a=7a+16 | | v/-4=13 | | -0.25+0.6= | | -0.25-0.6= | | (13m-11)=2m+5 | | -6(b-6)+4=88 |